2004
DOI: 10.1111/j.1600-079x.2004.00177.x
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptophan is a more potent in vitro hydroxyl radical scavenger than melatonin or vitamin C

Abstract: Hydroxyl radicals are involved in direct damage of important biomolecules. Potent radical scavengers such as vitamin C and indoles of the tryptophan family can avert the potential damage. Melatonin and its precursor 5-hydroxytryptophan (5-HTP) were compared with water-soluble vitamin C. Different scavenger concentrations were measured in a steady-state luminol chemiluminescence system (SLCL-system) with combined Fe(II) chloride (0.1 mm) and hydrogen peroxide (1.0 mm) as hydroxyl radical generators. 5-HTP showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 48 publications
2
21
1
Order By: Relevance
“…5-OH-tryptophan, the precursor of N-acetylserotonin and melatonin, was the most efficient radical scavenger in our experiments. In this regard, in a recent paper it has been demonstrated that 5-OH-tryptophan is a more potent in vitro hydroxyl radical scavenger than melatonin or vitamin C [85]. The free-radical scavenging potentials of the indole derivatives at different concentrations were also analyzed by the DPPH method and the results indicate that the indoles: 5-OH-tryptophan and N-acetylserotonin exhibited a dose-dependent free-radical scavenging ability at all of the tested concentrations.…”
Section: The Effect Of Melatonin and Structural Analogues On The Lipimentioning
confidence: 95%
“…5-OH-tryptophan, the precursor of N-acetylserotonin and melatonin, was the most efficient radical scavenger in our experiments. In this regard, in a recent paper it has been demonstrated that 5-OH-tryptophan is a more potent in vitro hydroxyl radical scavenger than melatonin or vitamin C [85]. The free-radical scavenging potentials of the indole derivatives at different concentrations were also analyzed by the DPPH method and the results indicate that the indoles: 5-OH-tryptophan and N-acetylserotonin exhibited a dose-dependent free-radical scavenging ability at all of the tested concentrations.…”
Section: The Effect Of Melatonin and Structural Analogues On The Lipimentioning
confidence: 95%
“…5), which is converted to 5-hydroxytryptophan (5-HTP), serotonin, N-acetyl serotonin, and then finally to MLT [1]. The differences of the hydroxyl scavenging behavior of these indole derivatives and vitamin C were studied [60]. 5-HTP was the most efficient radical scavenger when compare with MLT and vitamin C. Vitamin C was also more efficient than MLT and similar to 5-HTP.…”
Section: Loomentioning
confidence: 98%
“…Thus, whilst this agent has the potential of promoting the Fenton reaction, it also scavenges the hydroxyl radical and, at the same time, reduces the consequent rise in Fe 2+ -induced lipid peroxidation. Since hydroxyl radical cannot be detoxified enzymatically, antioxidants have evolved as endogenous scavengers to provide on-site protection against oxidative damage [60]. One such group of defense factors are indoles, which are derived from the essential amino acid tryptophan and reduce free radicals non-enzymatically by electron donation [93,94].…”
Section: -Lohmentioning
confidence: 99%
“…5-OH-tryptophan, the precursor of N-acetylserotonin and melatonin, was the most efficient radical scavenger in our experiments. In this regard, in a recent paper it has been demonstrated that 5-OH-tryptophan is a more potent in vitro hydroxyl radical scavenger than melatonin or vitamin C (Keithahn and Lerchl, 2005). The free-radical scavenging potentials of the indole derivatives at different concentrations were also analyzed by the DPPH method, and the results indicate that the indoles: 5-OHtryptophan and N-acetylserotonin exhibited a dose-dependent free-radical scavenging ability at all of the tested concentrations.…”
Section: Discussionmentioning
confidence: 95%